Behavioral political economy: a survey - Schnellenbach, Jan; Schubert, Christian (CESifo working papers, 2014)
Explaining individual behavior in politics should rely on the same motivational assumptions as explaining behavior in the market: That’s what Political Economy, understood as the application of economics to the study of political processes, is all about. In its standard variant, those who played the game of politics should also be considered rational and selfinterested, unlike the benevolent despot of earlier models. History repeats itself with the rise of behavioral economics: Assuming cognitive biases to be present in the market, but not in politics, behavioral economists often call for government to intervene in a "benevolent" way. Recently, however, political economists have started to apply behavioral economics insights to the study of political processes, thereby re-establishing a unified methodology. This paper surveys the current state of the emerging field of "Behavioral Political Economy" and considers the scope for further research.
Literaturverz. S.43-54